IFN-γ-INDUCED PROTEIN 10 (IP-10) IN RHEUMATOID ARTHRITIS: LITERATURE REVIEW AND THE AUTHORS' OWN DATA - A. S. Avdeeva (Научно-практическая ревматология, 2018)
Rheumatoid arthritis (RA) is a systemic autoimmune inflammatory disease characterized by chronic inflammation of joint synovial membrane and progressive destruction of bone and cartilage. Massive synovial infiltration with immune and inflammatory cells, such as macrophages, monocytes, granulocytes, plasma cells and dendritic cells, B lymphocytes, CD4+ and CD8+ T lymphocytes, presented mainly by effector T cells (Teff), underlies chronic inflammation and joint destruction in RA. C-X-C-chemokine 10 (CXCL10) was originally identified as a chemokine secreted by several types of cells: macrophages, endothelial cells, and fibroblasts in response to the production of interferon-γ (IFN-γ). It is also known as IFN-γ- induced protein 10 (IP-10). It has been recently discovered that the level of CXCL10 is elevated in the serum and joint tissues of laboratory animals with collagen-induced arthritis. Patients with RA demonstrated higher serum, synovial fluid, and synovial tissue levels of IP-10 than those with osteoarthritis or healthy donors at both early and late stages of the disease. Peripheral blood IP-10, unlike acute-phase measures or indices of activity, may more accurately reflect remission status, which should be kept in mind while deciding for therapy optimization. IP-10 may be a marker for more severe disease and can be used to assess the risk of psoriatic arthritis in patients with psoriasis; its prognostic value in patients with probable RA requires further clarification. Elevated IP-10 levels may be associated with the development of interstitial lung disease in patients with RA and identified in asymptomatic early-stage patients. Thus, IP-10 may be a useful and promising prognostic marker in RA, the significance of which requires further investigation.